2015
DOI: 10.1128/aac.04238-14
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Challenges in Treating Multidrug-Resistant Gram-Negative Bacteria: Resistance to Ceftazidime-Avibactam in Archived Isolates of Pseudomonas aeruginosa

Abstract: e Pseudomonas aeruginosa is a notoriously difficult-to-treat pathogen that is a common cause of severe nosocomial infections. Investigating a collection of ␤-lactam-resistant P. aeruginosa clinical isolates from a decade ago, we uncovered resistance to ceftazidimeavibactam, a novel ␤-lactam/␤-lactamase inhibitor combination. The isolates were systematically analyzed through a variety of genetic, biochemical, genomic, and microbiological methods to understand how resistance manifests to a unique drug combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
95
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 61 publications
7
95
0
Order By: Relevance
“…In addition, a small number of isolates with ceftazidimeavibactam MIC values of Ͼ8 g/ml that appeared to lack the transferable metallo-␤-lactamases screened as part of this study were identified, indicating the existence of yet undetermined antimicrobial resistance mechanisms against ceftazidime-avibactam. These mechanisms might include modifications of ␤-lactamase or penicillin-binding protein (PBP) sequences or changes in drug efflux levels (28)(29)(30)(31). Recently, a KPC-3-producing MDR K. pneumoniae isolate with a ceftazidime-avibactam MIC value of 32 g/ml was reported by others (32).…”
mentioning
confidence: 99%
“…In addition, a small number of isolates with ceftazidimeavibactam MIC values of Ͼ8 g/ml that appeared to lack the transferable metallo-␤-lactamases screened as part of this study were identified, indicating the existence of yet undetermined antimicrobial resistance mechanisms against ceftazidime-avibactam. These mechanisms might include modifications of ␤-lactamase or penicillin-binding protein (PBP) sequences or changes in drug efflux levels (28)(29)(30)(31). Recently, a KPC-3-producing MDR K. pneumoniae isolate with a ceftazidime-avibactam MIC value of 32 g/ml was reported by others (32).…”
mentioning
confidence: 99%
“…Bacterial resistance to one or more antibiotics occurs by various mechanisms (24)(25)(26). In this way, EMFs as an environmental agent could influence cellular responses such as antimicrobial susceptibility through different pathways (4,20,22,23,27).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies revealed that the emergence of resistance occurs at lower frequency than with other agents, and it is linked to specific mutations leading to the structural modification of AmpC-or efflux-related mechanisms in the case of ceftazidimeavibactam (9,(27)(28)(29)(30). In this work, we describe one further mechanism for development of resistance to these new antibiotics, through the selection of extended-spectrum mutations from narrow-spectrum OXA ␤-lactamases, such as OXA-2, which is relatively frequent among P. aeruginosa isolates worldwide (31).…”
mentioning
confidence: 99%